Video Games and the Transhuman Inclination - Geraci, Robert M. (Zygon, 2012)
Video games and virtual worlds play substantial roles in contemporary transhumanism. Many transhumanists appreciate the freedom and power that accompany these digital landscapes and recognize that they can promote transhumanist ways of thinking beyond the borders of explicitly transhumanist groups. Video games and virtual worlds enable transcendence through their design and contribute to transhumanism through the options they enable and the influence they have. Because of their significant place in transhumanism, video games and virtual worlds are thus important to the study of religion and science in the twenty-first century.